132 Short-term and long-term intake of high-level pea fiber specifically affects the bacterial community and metabolites in the cecum of pigs. (5th December 2019) - Luo, Yuheng; Chen, Hong; Yu, Bing; He, Jun; Zheng, Ping; Mao, Xiangbing; Luo, Junqiu; Huang, Zhiqing; Chen, Daiwen
Abstract: Current study was conducted to investigate the influence of short-term and long-term feeding of high-level pea-hull fiber (PF) on the bacterial community and metabolites in the cecum of pigs. A total of 50 healthy weaned Duroc × Landrace × Yorkshire piglets (7.2 ± 0.5 kg) were selected and randomly allocated in two groups with 5 replicates (5 piglets per replicate) in each group. Pigs in control group were given basal diets. For pigs in another group, expanded corn in the basal diet was replaced by PF at 10%, 20% or 30% for the post-weaning period (from weaning to 30 d post-weaning), growing period (30–90 d post-weaning), and finishing period (90–160 d post-weaning), respectively. At the end of the first and the last period, one pig from each replicate was sacrificed and the cecal digesta was collected immediately. Results showed that: 1) short-term or long-term intake of high-level PF had no significant effect on the ADFI and ADG of the pigs (P > 0.05), but the F/G was significantly decreased in the long-term fed pigs (P < 0.05). 2) The long-term feeding of PF significantly increased the concentration of cecal volatile fatty acids and decreased the ratio of propionate (P < 0.05). 3) Compared with control group, the ratio of phylum Firmicutes in the cecum of piglets with short-term feeding of PF was reduced by 5.6%, with an increase of Bacteroides-Prevotella-Porphyromonas (BPP), Enterococcus, Clostridium cluster IV, Bacteroidetes, Lactobacillus and Desulfovibrio desulfuricans (P < 0.05). While in the cecum of pigs with long-term feeding of PF, the ratio of phylum Bacteroidetes was increased by 4.8%, with an increase of D. desulfuricans (P < 0.01) and a decrease of BPP, Helicobacter-Flexispira-Wollinella, Streptococcus, Enterococcus and Clostridium cluster I (P < 0.05). Results indicate that bacteria in the hindgut of pigs can rapidly response to the high-level PF in the diet.